Analysis of the effect of a microcontroller-based solar panel cooling system on temperature and power output - Vicky Andria Kusuma; Happy Aprillia; Sena Sukmananda Suprapto; Muhammad Nizhom Ramadhani; Aji Akbar Firdaus; Dimas Fajar Uman Putra (Institute of Advanced Engineering and Science, 2023)
This research addresses the problem of temperature fluctuations affecting the efficiency of solar panels. A cooling system has been developed using a Peltier and a combination of air- and water-cooling methods. The air-cooling system involves placing a Peltier coated with a heatsink under the solar panel, while the water-cooling system uses pumped water on the panel's surface. The study aims to design a solar panel cooling system to reduce temperature and power losses and compare its output to standard solar panels. The system includes a Peltier, DC fan, and heatsink. Results indicate that the air-cooling system reduced temperature losses on the bottom milk of solar panels by 14.5%. However, the surface of solar panels showed no reduction in temperature losses. Additionally, solar panels with cooling systems were able to reduce power losses by 4% compared to standard solar panels. This research suggests that the use of an air-cooling system utilizing Peltier as the cooling medium could be a potential solution to reduce temperature losses and power losses on solar panels.